THE RELATIONSHIP OF AGE AND PARITY WITH ANEMIA IN PREGNANT WOMEN IN THE TEMBILAHAN HULU PUBLIC HEALTH CENTER - Sari, Nurul Indah; Arsita, Yuni (Infokes, 2019)
Pregnancy anemia is called "potential danger to mother and child" (potentially endangering the mother and child). The results of the Basic Health Research (Riskesdas) in 2016 stated that the prevalence of anemia in pregnant women in Indonesia was 37.1%. This study aims to determine the relationship between age and parity with the incidence of anemia in pregnant women in the UPT Puskesmas Tembilahan Hulu. Analytical descriptive research design with a case control approac. The sampling technique in the case group used a total sampling of 306 cases. Whereas for the control group using sistematic random sampling as many as 306 cases. The data collected is secondary data using a checklist. There is a relationship between age and incidence of anemia p value = 0,000 with OR 13,277 and there is a parity relationship with the incidence of anemia p value = 0,000 with OR 12,592. This research is expected to reduce the incidence of anemia, as well as being an input in services and care for pregnant women to make regular vitis who have their pregnances examined at the upstream healt clinik in the UPT Puskesmas Tembilahan Hulu.